Calf rearing profile in agrarian reform settlements in santana of livramento, RS, Brazil (Bioscience Journal, 2020)
In agrarian reform settlements there are obstacles in the rearing of calves; however, the main aspects that cause this obstacle are not known. Thus, the aim of this study was to diagnose the main obstacles in the management of these dairy heifers to target extension actions. For this, semi-structured guided questionnaires were applied to 40 families from 20 settlements. The questionnaire contained questions about the characteristics of the family, property and general management, feeding and sanitation of calves. The data were tabulated in Excel, transformed into variables and studied by means of multivariate analysis of main components after the farms were grouped into clusters according to similarity. The variables that most affected the heifer rearing system in dairy farms in the agrarian reform settlements of Santana do Livramento, RS, Brazil, were related to diet and occurrence of diarrhoea in calves. The 40 farms studied were grouped into six clusters, which differed especially in relation to who was responsible for the management of the heifers inside the property, regarding the infrastructure for the calves, time in milk production and concern regarding the care in the breeding of the calves. Based on these differences between the clusters being correctly identified, the technicians who work in these farms can establish strategies to work with settled families, emphasising the points where the obstacles are known to trigger the survival of heifers that will replace the dairy herds.